Critical Properties and Complexity Measures of Read-Once Boolean Functions - Lozin, Vadim; Moshkov, Mikhail (Annals of mathematics and artificial intelligence, 2021)
In this paper, we define a quasi-order on the set of read-once Boolean functions and show that this is a well-quasi-order. This implies that every parameter measuring complexity of the functions can be characterized by a finite set of minimal subclasses of read-once functions, where this parameter is unbounded. We focus on two parameters related to certificate complexity and characterize each of them in the terminology of minimal classes.